Teaching Academic English Corpus Trough Word-formation - Irina B. Korotkina (Moscow Polytechnic University, 2019)
Classical elements permeate global academic discourse and scientific terminology. Understanding the meanings and functioning of these elements can help multilingual scholars cope with disciplinary literature and write for publication and is therefore essential in teaching English for academic and specific purposes. However, few manuals on academic vocabulary explore word-formation in-depth or use it as a tool to alleviate learning through analysis and synthesis rather than memorizing words. Russian, as many other European languages, is a synthetic language in which affixation is as productive as in Latin. The paper presents a well-designed and approbated course of academic vocabulary for social scientists, analyses relationships between linguistic studies and teaching academic vocabulary, and discusses the ways of increasing the effectiveness and clarity of teaching by more systematic study of classical elements, enhancing students' analytical skills through innovative methodology and using the advantages of similarities between Russian and Latin word-formation. Comparative analysis demonstrates that the key features of the course, such as interactive computer-based visual materials and various analytical tasks involving students' background knowledge and academic awareness, help students not only decipher unknown words, but also produce neologisms, which is essential in coping with new terminology. Published as a book, Academic Vocabulary for Social Sciences is now available for teachers, students and researchers as a resource for study and self-study. The effectiveness of the approach demonstrates that it can be used as a model to design similar specific vocabulary courses for students of other synthetic languages.